2005
DOI: 10.1111/j.1600-0447.2005.00585.x
|View full text |Cite
|
Sign up to set email alerts
|

Executive functioning in depressed patients with suicidal ideation

Abstract: Depressed individuals contemplating suicide have cognitive rigidity, which does not appear to be a global brain dysfunction. Suicidal mental states may result from dysfunctional executive decision-making that is associated with the frontal lobe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
153
2
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(164 citation statements)
references
References 43 publications
4
153
2
5
Order By: Relevance
“…The present study links executive dysfunction with the emergence of suicidal ideas rather than their implementation. Marzuk and colleagues (16) similarly found that current suicidal was related to executive deficits regardless of history of suicidal behavior. Later, Westheide et al (14) also found that only suicide attempters with current suicidal ideation, compared to attempters with no current suicidal ideation displayed cognitive impairments in decision-making and motor inhibition (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study links executive dysfunction with the emergence of suicidal ideas rather than their implementation. Marzuk and colleagues (16) similarly found that current suicidal was related to executive deficits regardless of history of suicidal behavior. Later, Westheide et al (14) also found that only suicide attempters with current suicidal ideation, compared to attempters with no current suicidal ideation displayed cognitive impairments in decision-making and motor inhibition (31).…”
Section: Discussionmentioning
confidence: 99%
“…Marzuk et al (16) examined the association between current suicidal ideation and neuropsychological functioning by comparing a group of adults who were seriously contemplating suicide (60% with past suicide attempts) with a group of non-suicidal depressed participants (40% with past suicide attempts). The group with current suicidal ideation performed worse on several measures of executive function, specifically on tasks assessing set-shifting (e.g., the WCST, Trails Making Test Part B, and the Mazes subtest of the Wechsler Adult Intelligence Scale III), but showed no impairment on other cognitive measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prefrontal areas of the brain, which are responsible for the evaluation of changing alternatives and the execution of plans, are often implicated in executive tasks. 14 Most executive functions are linked to the dorsolateral prefrontal cortex, whereas response inhibition is associated with the orbitofrontal region. 15 …”
mentioning
confidence: 99%
“…A study comparing depressed patients with and without suicidal ideation showed that those with ideation performed significantly worse on some measures of reasoning and flexibility, but not on a test of inhibition. 14 Other analyses have yielded no significant relationships between neuropsychological performance and measures of suicidality in patients with depression and psychotic disorders, leading some to hypothesize that suicidality is a separate domain that is distinct from psychiatric symptomatology and neurocognitive performance. 23,24 …”
mentioning
confidence: 99%